Evaluation of a printed newsletter tailored to grandparent caregivers in Kansas - Brenes Mendieta, Priscilla (Kansas State University, 2017)
Millions of U.S. grandparents are responsible for providing parental care, in the absence of the biological parent, for at least one grandchild under the age of 18 years. These caregivers may base their wellness and nutrition practices with their grandchildren on outdated advice. In 2010, Kansas State University Human Nutrition Cooperative Extension Service faculty launched a theory-based newsletter, entitled Nourishing the Next Generation, that was mailed six times per year to low-income grandparent caregivers, and posted on a public website (at http://www.k-state.edu/humannutrition/newsletters/nourishing-the-next-generation/index.html). Each issue disseminated small amounts of practical, specific, “how-to” nutrition- and wellness-related information that addressed topics identified as being of concern to this population and that used recommended word choice, format, and design principles. After five years of Nourishing the Next Generation being in circulation, we surveyed readers who had received it from one to five years in order to assess the impact it had and to highlight its strengths. This study combined qualitative and quantitative approaches by using written surveys with both open- and closed-ended questions. Two different types of participants who had received the newsletter, grandparent caregivers and community educators, received surveys. A total of 54 valid surveys were returned from the 492 that were sent to grandparent caregivers, while 30 out of 175 community educators completed surveys. The newsletter was perceived by responding grandparent caregivers to be very effective in improving their awareness, knowledge, motivation, and confidence to follow recommendations about healthy eating and physical activity. Also, reading it led to many self-reported positive changes in various nutrition, physical activity, and other wellness practices among 91 percent of the responding grandparent caregivers and their families. In addition, 70 percent of responding community educators used its contents extensively to disseminate information to wider audiences. In conclusion, including grandparent caregivers in wellness-related educational programs could be a good approach to target healthy lifestyle practices of both older and younger generations. An appropriately designed newsletter can effectively improve the health of a large number of people, yet has limited costs, and thus, is an excellent public health method.
Keywords: Nutrition education; Evaluation; Newsletter; Grandparents; Skipped generation